Hematologic Abnormalities After COVID-19 Infection: A Case of Coombs-Negative Hemolytic Anemia and Thrombocytopenia - Alanna Glidden Siegenthaler MD; Ghanshyam Ghelani MBBS; Amy Brady DO; Taylor Loon MBBCh; Bhaskara Reddy Madhira MBBS (SAGE Publishing, 2023)
The occurrence of hemolytic anemia in patients with active SARS-CoV-2 infection has been documented in medical literature. While relatively uncommon, there have been instances where this condition presents as a Coombs-negative hemolytic anemia. In this research study, we report a distinctive case of Coombs-negative hemolytic anemia and thrombocytopenia in a patient with a known history of COVID-19 infection. The patient demonstrated a favorable response to treatment involving the administration of steroids and intravenous immunoglobulin (IVIG) therapy. This case adds to the existing body of evidence regarding the hematological manifestations of SARS-CoV-2 infection, highlighting the importance of considering and managing hematological complications in patients with COVID-19.